Confronting Nollywood’s Hegemony In Ghana: A Historical Perspective Of Akan Video Movies In Ghana - Ohene-Asah, R. (Ghana Studies, 2022)
The literature on Ghana’s cinema practices have focused primarily on the English-language film industry centralized in the capital, Accra. The last two decades, however, witnessed a significant rise in Akan-language videos originating largely from Kumasi in the Ashanti Region of Ghana. The number of movies produced and the audience reception resulted in a decline in circulation of the Accra English-language movies as well as those from Nollywood, which dominated the African film spectrum. Despite these successes, the Akan video industry is largely understudied. This article relies on observations and interviews with practitioners within the Kumasi film production enclave to suggest that the adoption of indigenous languages for film is consequential to the break in former Nollywood film dominance in Ghana. I examine key historical accounts and the nature of the Akan video film industry as a countermovement to the status quo as well as a cultural resistance strategy that successfully challenged the Nollywood hegemony, which stretched throughout the continent and beyond.
Research Article
Keywords: Akan language videos; Nollywood; Ghana Akan films